2020
DOI: 10.1038/s41467-020-15519-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the surface evolution of LaTiOxNy an oxynitride solar water splitting photocatalyst

Abstract: LaTiO x N y oxynitride thin films are employed to study the surface modifications at the solidliquid interface that occur during photoelectrocatalytic water splitting. Neutron reflectometry and grazing incidence x-ray absorption spectroscopy were utilised to distinguish between the surface and bulk signals, with a surface sensitivity of 3 nm. Here we show, contrary to what is typically assumed, that the A cations are active sites that undergo oxidation at the surface as a consequence of the water splitting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…The LaTiO 2 N thin film developed a net photocurrent of approximately 20 mA cm À2 at 1.23 V vs. RHE. The photocurrent is comparable with the LaTiO 2 N film deposited on MgO/TiN and Nb:SrTiO 3 substrates via PLD and RF sputtering reported by Lippert 29 and Domen, 26 respectively. The dark-current contribution stems from photocorrosion of the oxynitride surface, which is a common phenomenon for unprotected metal oxynitrides and can be suppressed with protective layers.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The LaTiO 2 N thin film developed a net photocurrent of approximately 20 mA cm À2 at 1.23 V vs. RHE. The photocurrent is comparable with the LaTiO 2 N film deposited on MgO/TiN and Nb:SrTiO 3 substrates via PLD and RF sputtering reported by Lippert 29 and Domen, 26 respectively. The dark-current contribution stems from photocorrosion of the oxynitride surface, which is a common phenomenon for unprotected metal oxynitrides and can be suppressed with protective layers.…”
supporting
confidence: 81%
“…[22][23][24] This renders semi-transparent quaternary metal oxynitrides generally as very promising photoanode candidates for PEC tandem cells, which could outperform Ta 3 N 5 -based devices. So far, semi-transparent quaternary metal oxynitride films have been mainly fabricated by means of reactive radiofrequency (RF) magnetron sputtering [25][26][27][28] or pulsed laser deposition (PLD) 29,30 on MgO or Nb:SrTiO 3 substrate. In case of the RF approach, the oxynitride sputtering targets have to be made first with multi-step processes, and harsh conditions (usually up to 1073 K for film deposition) are required, too.…”
mentioning
confidence: 99%
“…[263][264][265][266][267] Advances in this field have shown that the apparently stable perovskites can indeed transform into other phases when exposed to the corrosive conditions of water splitting. [268][269][270][271][272] Suntivich et al showed that in the initial stages of the catalysis, the crystalline Ba 0.5 Sr 0.5 Co 0.8 -Fe 0.2 O 3Àd mixed oxide (BSCF) changes and forms an amorphous mixed oxide shell on the surface, which acts as the true catalyst in the OER ( Fig. 14a-d).…”
Section: Challenges In the Mechanistic Investigation Of Heterogeneousmentioning
confidence: 99%
“…Lawley et al used TiN as the substrate and coated with MgO for deposition, and finally obtained LaTiO x N y (x + y = 3) thin films to study the surface modification of the solid-liquid interface during the photocatalytic water splitting. 59 The structure and morphological characteristics of LaTiO x N y thin film are shown in Fig. 7.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%